Peningkatan Teknologi Pendidik Pesantren Anak Sholeh melalui MEMRiSE: Coaching & Training - Hesty Puspita Sari; Wawan Herry Setiawan (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2021)
Mastering technology improvement is something that educators have to continue to strive for on an ongoing basis. A teacher is required to master the use and applicate the science and technology development along the revolution industrial era 4.0. To continue improving the quality of self, a teacher needs to be given coaching and training. The training activity with the theme